A comparison of Land Use Change models: challenges and future developments. (1st February 2016) - De Rosa, Michele; Knudsen, Marie Trydeman; Hermansen, John Erik
Abstract: Land demand is driven by an increasing population and changing consumption patterns. When land is required Land Use Changes (LUC) are triggered, causing several environmental and social impacts. Particularly topical is the assessment of indirect LUC effects. Several methodological approaches have been proposed for carrying out the assessment. In this paper we classified LUC models for Life Cycle Assessment (LCA) applications into three main categories: Economic, Causal–Descriptive and Normative models. Six models were selected as representative of these three categories and compared according to fifteen criteria covering: modeling framework, impact categories assessed and model transparency. The results show that, progresses have been made in the Economic General Equilibrium Models and the Causal–Descriptive Models compared. Causal–Descriptive models appear more suitable for long-term assessments in the LCA context while the compared economic models are more suitable for short/medium-term assessments of LUC consequences. As LUC dynamics involve interdisciplinary knowledge, a combination of economic, biophysical and statistical data is however required to achieve a robust assessment of complex LUC dynamics. There is still considerable scope for improving current LUC models. In particular, there is room for improving precision of data, identification of marginal land and inclusion of a broader range of impact categories. Current models mainly focus on GHG emission-related impacts and rarely on other environmental impacts such as nutrient leaching, biodiversity impacts and water resource depletion. Socio-economic analyses of LUC patterns are currently excluded from LCA analysis, preventing a holistic assessment of land occupation impacts.